Granular Cell Tumor of the Anal Canal: Case Report and Literature Review - Prats, Jorge Arche; Prado, Diego García; Villegas, Gonzalo Campaña; Mardónez, Mónica Martínez (Journal of Coloproctology, 2024)
Granular cell tumors (GCTs) are rare benign neoplasms that can occur anywhere in the body but are most commonly found in the head and neck region. These tumors are often asymptomatic and are incidentally discovered during routine rectal examination. In some cases, symptoms may include bleeding, pain, and a palpable mass. Imaging studies such as colonoscopy, ultrasound, magnetic resonance imaging (MRI), or computed tomography can be used to characterize and measure the tumor. Treatment typically involves local resection, with or without adjuvant radiotherapy, depending on the size, location, and pathological characteristics of the tumor. The prognosis for GCTs of the anal canal is generally good, with few cases of recurrence or metastasis reported, but long-term follow-up is recommended due to the potential for late recurrence or malignant transformation. The present study reports a 39-year-old female patient who presented with anal itching associated with protrusion of a perianal mass and who underwent treatment between November 2022 and December 2023. The MRI scan revealed a nodular image in its caudal aspect with involvement of the internal sphincter between 12 and 5 o'clock, which was successfully resected. Histopathology was compatible with GCT, and the patient had a satisfactory recovery and was discharged. In conclusion, GCTs of the anal canal are rare and extremely unusual tumors that can be difficult to diagnose and manage, requiring a multidisciplinary approach for optimal management.
Keywords: granular cell tumor; anal canal; neoplasm; diagnosis; prognosis